The Relationship Between Platelet Collagen Receptor Glycoprotein VI and No- Reflow Phenomenon in Patients With Acute ST- Segment Elevation Myocardial Infarction - Kobat, Mehmet Ali; Balin, Mehmet; Celik, Ahmet; Baydas, Adil; Dagli, Mustafa Necati (Bmj Publishing Group, 2014)
Background and Aim Vitamin D deficiency is common and may contribute to cardiovascular diseases. We hypothesized that serum 25-hydroxyvitamin D [25(OH)D] levels would be inversely associated with inflammation and with diastolic dysfunction. We therefore investigated the link between serum vitamin D levels (i) echocardiographic measures and (ii) inflammatory parameters. Methods The cross-sectional study included 281 patients who were referred to coronary angiography for stable angina pectoris. Patients were recruited between December 2010 and November 2011. Patients with established congestive heart failure, gout, chronic kidney disease (estimated glomeruler filtration rate <60 mL/min per 1.73 m(2)), and acute infection were not included. We measured serum 25(OH)D levels, C-reactive protein and fibrinogen levels. A radioimmunoassay procedure was used to measure 25(OH)D (DiaSorin, Stillwater, MN). We also performed standardized left ventricular (LV) echocardiograms, and echocardiographic data were used for classification of systolic and diastolic dysfunction. We analyzed the relation between serum levels of 25(OH)D and inflammatory markers and echocardiographic measures of LV mass and diastolic dysfunction. Results At baseline, subjects had a mean age of 59.5 10 years, and 43.4% were women. Left ventricular mass index, left atrial diameter, isovolumic relaxation time, and E/E ratio were significantly higher in patients with lower 25(OH)D levels. In ordinal logistic regression analysis, higher 25(OH)D was negatively associated only with LV mass index (odds ratio [OR], 0.965; 95% confidence interval [95% CI], 0.939-0.992; P = 0.015), isovolumic relaxation time (OR, 0.962; 95% CI, 0.939-0.985; P = 0.001), E/E ratio (OR, 0.874; 95% CI, 0.811-0.942; P = 0.008), and C-reactive protein (OR, 0.802; 95% CI, 0.668-0.962; P = 0.021). Conclusions Serum levels of 25(OH)D are significantly associated with LV diastolic dysfunction and LV mass index, although the effect size is rather small. Longitudinal studies in larger populations are needed to establish firmly or refute a causal relationship between vitamin D levels and diastolic dysfunction and LV mass index.
Keywords: vitamin D; diastolic dysfunction; E; E ratio; left ventricular mass index; C-reactive protein